Osteoarticular mucormycosis of the distal femur in a post COVID-19 patient - Srinivas Kasha; Venugopal Palakurthi; Ranjith Kumar Yalamanchili; Patil Pratik Yashavant; Rohith GPRK (Medical Mycology Case Reports)
A 38 year old man with no known comorbidities presented with pain and swelling over the knee joint a few days after recovery from severe COVID-19. Initial debridement and cultures revealed growth of Mucorales affecting a large segment of the distal femur with also positive cultures obtained from the maxillary sinus and the lower lobe of the right lung. Due to this involvement of a long segment of the femur, right lung and left maxillary sinus, a multidisciplinary approach of above knee amputation along with debridement of left maxillary sinus and lobectomy of right lung lower lobe was performed to decrease the fungal load and favour good prognosis. This report warrants the need for early imaging and surgical debridement of tissue for fungal cultures and biopsy in immunocompromised individuals.